The Fate of the Land and the People in Maskhur Zhusup Kopeyev’s Publicistic Work - Batkeyeva Б.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
M.Zh. Kopeyev left to his descendants a rich creative heritage in the field of history, literature, ethnography, and journalism. Many scholars, historians, writers and publicists turned to the study of his many-sided creativity. His works are the basis of many doctoral, candidate, master theses, graduation works, scientific articles and publications. M.Zh. Kopeyev’s creativity even today can serve as a source of scientific research in various fields of culture, literature, and history. A special stand in M.Zh. Kopeyev’s creativity is journalism. These are scientific works on the history, folklore of the Kazakh people, articles on the social, economic, political life of the Kazakh people, peculiarities of the way of life and manners, national psychology, education, and upbringing. The article deals with M.Zh. Kopeyev’s poetry collections “Who Owns Saryarka” and “Wonderful Impressions from Many Years of Experience”, where in a special verse form we can see a realistic picture of the life of Kazakhs of the early XX century